Facteurs et modalités d’insertion des activités productives entre tissus urbains et parcs d’activité économique - Alexis Gilbart; Kristel Mazy (EchoGéo)
At the crossroads of the issues of reindustrialization and land sobriety, this article questions the practices of economic development through the methods of inserting productive activities within urban fabrics and economic activity parks. How does a regional desire for reindustrialization translate locally? If the question of reindustrialization in small and medium-sized towns is inseparable from a better understanding of the local entrepreneurial ecosystem, on the one hand, and from a better integration of the productive function in urban planning policies, on the other hand, what are the relational dynamics between production and territory? This study, carried out on the post-mining territories of Mons-Borinage, located in Belgium, addresses these questions in three stages: first by putting the territory into context, then by highlighting an empirical study carried out with 10 productive VSEs-PEs, imagined through the prism of the entrepreneur, and finally by putting these results into perspective by confronting the practices of economic development with the objectives of land sobriety.